(untitled) (Nigerian Journal of Technology, 2020)
The need to reduce energy consumption in production processes becomes paramount due to environmental effect of electrical energy sourced from fossil fuel. This research addresses this challenge in orthogonal turning of AISI 304 Alloy Steel. Orthogonal turning operations were carried out in dry and wet conditions using mineral oil based and vegetable oil based cutting fluids. While turning, the effect of input parameters which include cutting speed, feed rate and depth of cut on the energy consumption and surface roughness were studied and empirical models to enhance minimum energy consumption and surface roughness were proposed. Minitab 17 statistical software via RSM was used for experimental design. Multi-response optimisation was also carried out using GRA. The result shows the optimum cutting parameters for dry environment as cutting speed of 396.46 rev/min, feed rate of 1.17mm/rev and depth of 0.5mm. For wet turning with mineral oil based cutting fluid, the results are 600 rev/min cutting speed, 0.33mm/rev feed rate and 0.01mm depth of cut. Wet turning with vegetable oil based cutting fluid shows optimal combined process parameters of 600 rev/min cutting speed, 0.5mm/rev feed rate and 0.25mm depth of cut. ANOVA shows that in dry turning, depth of cut has the most significant effect of 83.11%, in wet turning with mineral oil based cutting fluid, cutting speed has the most significant effect of 38.87% while wet turning with vegetable oil based cutting fluid, feed rate shows the most significant effect of 52.44% http://dx.doi.org/10.4314/njt.v39i2.15